Experimental and correlation study of selected physical properties of aqueous blends of potassium sarcosinate and 2-piperidineethanol as a solvent for CO2 capture - Jaafar, Jafreezal (2017)
In this work, physical properties such as density, refractive index, and viscosity of aqueous blends of potassium sarcosinate (K-Sar) and 2-piperidineethanol (2-PE) were measured at temperatures ranging from 298.15 to 333.15 K. Several concentrations of K-Sar and 2-PE blends were prepared in terms of mass fraction (0.04 + 0.16, 0.08 + 0.12, 0.12 + 0.08, 0.16 + 0.04, and 0.20 + 0), respectively